Identification and Characterization of Potential Chalky Soil Plant Growth-Promoting Bacteria (PGPR) Isolated from the Rhizosphere of Chamaecytisus ruthenicus (Russian Broom) - Zekarias A. Asfha; Yulia Kocharovskaya; Nataliya E. Suzina; Tatiana N. Abashina; Valentina N. Polivtseva; Yanina Delegan; Inna P. Solyanikova (Biology and Life Sciences Forum)
Plant growth-promoting rhizospheric bacteria (PGPR) are well known for their significant roles in agriculture and the environment. In our previous study, 23 chalky soil bacterial isolates were obtained from the rhizosphere of Chamaecytisus ruthenicus. In total, seven out of them were reported for their potential effect on plant growth. However, the identification and further characterization of those chalky soil bacteria have not been completed yet. Therefore, the purpose of the present study is to identify and characterize chalky soil rhizospheric bacteria (seven previously investigated and one additional bacteria). A total of eight bacterial isolates were cultured in LB and other growth media to investigate their morphological behavior, antibiotic sensitivity or resistance status, and their effect on plant growth. Moreover, 16S rRNA gene sequencing was used to identify those potent bacterial isolates. The results of the present study demonstrate that all bacterial isolates obtained stable morphology in the three types of growth media. However, four bacterial isolates (Z11, Z12, Z15 and Z44) showed color change. The antibiotic test result also revealed that all the tested bacterial isolates except Z11 and Z24 were resistant to both ampicillin (10 μg) and oxacillin (1 μg), whereas all bacterial isolates were sensitive to polymyxin (300 units), amoxicillin (20 μg), vancomycin (30 μg), ceftazidime (30 μg), erythromycin (15 μg), ciprofloxacin (5 μg), bacitracin (10 units) and streptomycin (30 μg). The result of the growth stimulation effect revealed that few bacterial isolates had a stimulation effect on the germination rate of oats and lentils, on the shoot length of maize and oats, on the root length of wheats, maize and lentils, on the fresh weight of wheats and oats or on the dry weight of oat seeds. Furthermore, the 16S rRNA gene sequence analysis result revealed that the bacterial isolates belonged to Streptomycetes spp. and Jantinobacterium sp. To conclude, the potential chalky soil rhizospheric bacteria have a substantial impact on agriculture and the environment.